Penguatan Karakter Insani dan Ukhuwah Islamiyyah melalui Peringatan Maulid Nabi Berbasis Rumah di Desa Larike - Aminah Bahasoan; Asep Asep (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Noble human character and ukhuwah Islamiyyah are the main pillars in building a harmonious, religious and civilized society. Larike Village faces the challenge of declining community participation in religious activities, especially recitation and commemoration of the Prophet's birthday, which has the potential to weaken the social and moral values of the community. This community service aims to strengthen character and ukhuwah through an innovative approach by holding Maulid Nabi activities in rotation at residents' homes, integrating the exemplary value of the Prophet, Islamic parenting, and intensive social interaction. This participatory and cultural-based implementation method succeeded in reviving the collective spirit and strengthening awareness of the mother's role as an agent of family and community change. The results of the service showed a significant increase in religious spirit, quality of ukhuwah, and parenting awareness. This model proved to be effective, sustainable, and has the potential for replication in other communities facing similar challenges